Kyrgyzstan: Quality Assurance—Do State Standards Matter? - Merrill, Martha C (International Higher Education, 2016)
The Kyrgyz Republic has been without a formal system for evaluating its higher education institutions since June 3, 2014, but neither educators nor the public seem to care very much. Specific circumstances make the lack of formal assessment mechanisms at the national level less critical than might be the case elsewhere. Nevertheless, since one factor is that some of the stronger institutions have degrees recognized elsewhere and others are pursuing international accreditation, educators elsewhere might want to keep an eye on Kyrgyzstan.